The Hot Neptune WASP-166 b with ESPRESSO – I. Refining the planetary architecture and stellar variability. Issue 1 (4th August 2022) - Doyle, L; Cegla, H M; Bryant, E; Bayliss, D; Lafarga, M; Anderson, D R; Allart, R; Bourrier, V; Brogi, M; Buchschacher, N; Kunovac, V; Lendl, M; et al.
ABSTRACT: In this paper, we present high-resolution spectroscopic transit observations from ESPRESSO of the super-Neptune WASP-166 b. In addition to spectroscopic ESPRESSO data, we analyse photometric data from TESS of six WASP-166 b transits along with simultaneous NGTS observations of the ESPRESSO runs. These observations were used to fit for the planetary parameters as well as assessing the level of stellar activity (e.g. spot crossings, flares) present during the ESPRESSO observations. We utilize the reloaded Rossiter McLaughlin (RRM) technique to spatially resolve the stellar surface, characterizing the centre-to-limb convection-induced variations, and to refine the star–planet obliquity. We find WASP-166 b has a projected obliquity of $λ = -15.52^{+2.85}_{-2.76}\, ^{° }$ and v sin ( i ) = 4.97 ± 0.09 km s −1 which is consistent with the literature. We were able to characterize centre-to-limb convective variations as a result of granulation on the surface of the star on the order of a few km s −1 for the first time. We modelled the centre-to-limb convective variations using a linear, quadratic, and cubic model with the cubic being preferred. In addition, by modelling the differential rotation and centre-to-limb convective variations simultaneously, we were able to retrieve a potential antisolar differential rotational shear (α ∼ −0.5) and stellar inclination ( i * either 42.03$^{+9.13}_{-9.60}\, ^{° }$ or 133.64$^{+8.42}_{-7.98}\, ^{° }$ if the star is pointing towards or away from us). Finally, we investigate how the shape of the cross-correlation functions change as a function of limb angle and compare our results to magnetohydrodynamic simulations.